A Comparative Study Of The Flotation Performance Of Ores Treated In An Isamill And A Ball Mill - T. Khonthu (International Mineral Processing Congress, 2012)
The purpose of this investigation was to evaluate the relationship between different milling procedures, viz. a ball mill and an IsaMill respectively, and the flotation performance of the different mill products. Two ores were used, viz. a base metal sulphide (BMS) and a platinum group mineral (PGM) UG2 ore. Flotation was used as a diagnostic to investigate whether the different milling procedures may have different effects of the floatability of the particles. The present study is part of a research programme investigating this question using a wide range of comminutiondevices and procedures. Similar particle size fractions from the different milling procedures were used in the flotation tests. The particles were characterized in terms of particle size distribution, morphology (using scanning electron microscopy and image analysis software) and rheology tests. The results have shown that in general when comparing similar feeds to flotation in terms of equivalent particle size distributions as indicated by the d80 value, the ball mill generally yielded better recoveries and grades in the case of the BMS and lower chromite recoveries in the case of the UG2 ore compared to the IsaMill. No significant differences were observed in the morphological or rheological characteristics of the particles subjected to the different milling procedures. Although the results appear to indicate that IsaMilling is less advantageous than ball milling in terms of the flotation performance for the two ores studied it should be emphasized that these results do not take into account the relative advantage which IsaMilling has over ball milling in terms of direct and indirect energy consumption and GHG emissions nor, most importantly, does it consider the platinum group element recoveries in the case of the UG2 which may have increased significantly as a result of the finer grind which the IsaMill produces after 4 passes compared to the ball mill after 64 min. Such results which will be reported is due course may show that the greater liberation expected after IsaMilling of the PGMs outweighs any disadvantages indicated in this study.